Strategi Pemasaran Produk Simpanan Qurban dalam Menarik Minat Nasabah di BMT Mandiri Sejahtera Moropelang dan BMT Mandiri Sejahtera Sumberwudi Lamongan - Rizqiyani, Hanifah; Sari, Citra Mulya (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2023)
This study aims to find out how the marketing strategy activities for qurban savings products at BMT Mandiri Sejahtera Moropelang and BMT Mandiri Sejahtera Sumberwudi Lamongan. This qurban savings product is also a product that is rarely owned by other Islamic financial institutions. This qurban savings product uses a wadiah yad dhammanah contract and is planned. This qurban savings product makes its customers disciplined in saving because withdrawals can only be made as the time of sacrifice approaches. The research method uses qualitative data analysis which describes descriptively the marketing strategy activities for Qurban Savings Products at BMT Mandiri Sejahtera, Moropelang and Sumberwudi branches. The two BMT branches both carry out marketing activities for savings products using a marketing mix strategy or Marketing Mix to attract customers’ interest in raising funds for the purpose of sacrificial worship.